Surgical Evacuation Extradural Hematoma under Local Anesthesia - Aziz Qureshi, Peer Asad; Raja, Riaz A; Naim, Syed Khizr; Pathan, Sanaullah; Hassan, Shahzor; Jamali, G Murtaza (International Journal of Endorsing Health Science Research, 2017)
Extradural hematoma as a result of traumatic injury is a serious neurological emergency that required immediate intervention. The standard protocol is to identify the condition at earliest and provide quick surgical evacuation of the hematoma. The situation tends to be fatally deteriorating and marks a high mortality rate and worse health outcomes. We have presented a case of extradural hematoma in this study where the surgery had a delay due to the unavailability of general anesthesia. However, the falling Glasgow Coma Scale scores encouraged the surgeons to induce the surgical procedure with the employment of local anesthesia. The intervention turned out to be successful and produced the possibility of using local anesthesia as an alternative in case of critical emergency situations in order to save a life.